2013
DOI: 10.1007/s13139-013-0224-6
|View full text |Cite
|
Sign up to set email alerts
|

18F-FDG PET in Patients with Primary Systemic Anaplastic Large Cell Lymphoma: Differential Features According to Expression of Anaplastic Lymphoma Kinase

Abstract: Purpose Primary systemic anaplastic large cell lymphoma (ALCL) is divided into two entities according to the expression of anaplastic lymphoma kinase (ALK). We investigated 18 F-fluorodeoxyglucose positron emission tomography ( 18 F-FDG PET) findings in primary systemic ALCL according to ALK expression. Methods Thirty-seven patients who had baseline PET before CHOP (cyclophosphamide, doxorubicin, vincristine and prednisolone)-based chemotherapy were enrolled. Among them, patients who underwent interim and/or p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
8
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 26 publications
2
8
0
Order By: Relevance
“…Subsequently, ALK translocations were also found in other cancers, such as lung cancers [26]. The present study found that ALK-positive ALCL had a higher 18 F-FDG uptake than that of ALK-negative ALCL (SUVmax: 22.1 ± 14.3 vs. 15.1 ± 6.6, t = 2.354, P = 0.023), which was consistent with the results reported by Lee DY [9]. Similarly, ALK-positive lung cancers were also observed to have a higher SUVmax than ALK-negative [27,28] lung cancers.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…Subsequently, ALK translocations were also found in other cancers, such as lung cancers [26]. The present study found that ALK-positive ALCL had a higher 18 F-FDG uptake than that of ALK-negative ALCL (SUVmax: 22.1 ± 14.3 vs. 15.1 ± 6.6, t = 2.354, P = 0.023), which was consistent with the results reported by Lee DY [9]. Similarly, ALK-positive lung cancers were also observed to have a higher SUVmax than ALK-negative [27,28] lung cancers.…”
Section: Discussionsupporting
confidence: 92%
“…The present study revealed that ALCL had intense uptake of 18 F-FDG in tumours with a mean SUVmax of 19.5 ± 12.6. Due to the high 18 F-FDG uptake, PET/CT had a very high sensitivity for the detection of ALCL (98.0%), which was consistent with the results reported by Lee DY, et al [9]. High uptake of 18 F-FDG in the lesions implies that PET/CT is a perfect modality for staging and treatment response evaluation for ALCL.…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…One study has shown differences in extra-nodal sites involved in ALK-positive and ALK-negative ALCLs: bone marrow, bone, subcutaneous tissue, and splenic involvement were seen at more commonly in ALK-positive patients, whereas skin, liver, and gastrointestinal involvement was more frequent in ALK-negative ALCL (43). The degree of 18 FDG uptake is higher in ALK-positive ALCL than in ALK-negative ALCL, suggesting that PET may be useful in distinguishing between the two groups (45). …”
Section: Subtypes Of T-cell Nhlsmentioning
confidence: 99%